The image of dentist profession in the opinion of dentistry students of the Medical University of Lublin in 2004-2007 - Chałas, Renata; Bachanek, Teresa; Cieszko-Buk, Maria; Wójcik-Chęcińska, Ilona (Polish Journal of Public Health, 2011)
Introduction. Dentist profession is specific because of the requirements concerning personal predispositions, ways of behaviour and appearance acceptable by patients. Aim. The aim of the study was to know the motivation for studying and imaginations about dentist job among the second year dentistry students. Material and Methods. Three hundred and fourty seven dentistry students of the Medical University of Lublin were examined from 2004 till 2007 on the basis of questionnaire survey. The questions concerned the criteria of choosing the job, motivation, imaginations about dentist work, characteristics of dentists and their attributes. Results. On the basis of the performed study we noted that almost all dentistry students decided on their major of study themselves. The majority of examined students (93.03%-100%) indicated that dentists should be neat, clean, should work in an apron and have nice teeth. Conclusions. The examined dentistry students realize that dentist profession is difficult, tiring and requiring precision. They see dentist as a traditional profession of the common trust.